ARE SUSTAINABILITY DISCLOSURE AND TAX AVOIDANCE ASSOCIATED WITH THE COST OF DEBT? - Hutabarat, Paskah Deby Chabelita; Firmansyah, Amrie (Ultimaccounting Jurnal Ilmu Akuntansi, 2022)
Abstract” This study examines whether sustainability disclosure and tax avoidance affect the cost of debt. The research data was obtained from financial statements, annual reports and sustainability reports of property and real estate sub-sector companies in Indonesia listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2020. Data sourced from www.idx.co.id, www.idnfinancials.com and the authorized company's websites. Based on purposive sampling, the total sample used in this study amounted to 104 observations. Hypothesis testing is conducted by using multiple linear regression analysis for cross-section data. The study results conclude that sustainability disclosure and tax avoidance are not associated with the cost of debt. This research indicates that the Indonesia Financial Services Authority should increase supervision over sustainability and company policies to finance companies through debt made by listed companies. Keywords: Cost of Debt; Tax Avoidance; Corporate Social Responsibility